EFEKTIFITAS ATRAKTAN PADA FLY TRAP TERHADAPJUMLAH LALAT RUMAH (MUSCA DOMESTICA) - Putra, Fikri Kelana (JURNAL MEDIA KESEHATAN, 2013)
This studyaims to determine theeffectiveness oforganic wasteattractants, fish, andtempeh (fermented soybean cake)onthe flytraptothe number of fliesinthe housethatcaught in Fish Auction Place(TPI) PulauBaaiBengkulu city. The research methodis aQuasiExperiment(quasi experimental) research designPosttestOnly ControlGroupDesign. Research analysisusingOne WayAnovatestandfollowed byLSDtest. This studyuses12flytrapattractantaddition oforganic waste, fish, andfermented soybean cakethathas beendecomposedfor 7dayswith3repetitions. The results showedthe meannumber ofhouse flies(Musca domestica)werecaughtonthe flytrapwithattractantorganic waste152tail, fishtail240, and331tailtempeh. ANOVAtestresultsshow the value ofp=0.000<0.05 means thatthere is asignificant differencebetween thenumber of fliescaught in three attractants, andbased onthe results ofLSDis known that fermented soybean cake is themosteffectiveattractantstrapscompared with organic wasteandrotting fish attractant.